Tibetan medicine in the contemporary world: global politics of medical knowledge and practice - Pordié, Laurent (Routledge, 2008)
Tibetan medicine today: neo-traditionalism as an analytical lens and a political tool / Laurent Pordié -- Inventing tradition: Tibetan medicine in the post-socialist -- Contexts of China and Mongolia / Craig R. Janes & Casey Hilliard -- Place and professionalization: navigating amchi identity in Nepal / Sienna R. Craig -- The diffusion of Tibetan medicine in China: a descriptive panorama / Chen Hua -- Integration or erasure?: modernizing medicine at Lhasa's Mentsikhang / Vincanne Adams & Fei-Fei Li -- Hijacking intellectual property rights: identities and social power in the Indian Himalayas / Laurent Pordié -- Tibetan medicine and biodiversity management in Dolpo, Nepal: negotiating local and global worldviews, knowledge and practices / Yildiz Aumeeruddy-Thomas & Yeshi C. Lama -- The integration of Tibetan medicine in the United Kingdom: the clinics of the Tara Institute of Medicine / Colin Millard -- Tibetan medicine revisited in the West: notes on the integrative efforts and transformative consequences occurring in Massachusetts, USA / Ivette Vargas -- An ancient medicine in a new world: a Tibetan medicine doctor's reflection from 'inside' / Eliot Tokar -- The politics of Tibetan medicine and the constitution of an object of study: some comments / Geoffrey Samuel
Includes bibliographical references
Keywords: Aufsatzsammlung; Medizin; Tibet